Older people and responses to COVID‐19: A cross‐sectional study of prevention practices and vaccination intention. (30th November 2021) - Wong, Li Ping; Alias, Haridah; Tan, Yi Ru; Tan, Kit Mun
Abstract: Background: COVID‐19 is a threat to everyone's health and can be especially devastating to older individuals. Aim: This study examined the behavioural prevention practices against SARS‐CoV‐2 infection and the intention to vaccinate among older people when the COVID‐19 vaccine is on the verge of becoming available. Method: A cross‐sectional, online survey was conducted between 14th July and 8th October 2020 among the older people in Malaysia. A questionnaire was designed to assess the practice towards measures preventing SARS‐CoV‐2 infection, and COVID‐19 vaccination attitudes and intention. Socio‐demographic characteristics, constructs of a health belief model (HBM), the 6‐item state version of the State‐Trait Anxiety Inventory (STAI‐6) were correlates of the main outcomes. Findings: The mean score of total preventive measures scores was 13.4 ± 1.7 out of a maximum score of 15, indicating very good prevention practices. By demographics, females, having a tertiary education exhibited higher prevention practices in the univariable analyses. Components of the HBM and being female remain significant correlates of higher prevention practices in multivariable logistic regression analysis (MLRA). A total of 657 (87.1%) participants responded and intend to receive the COVID‐19 vaccination. Provider recommendations may improve vaccination uptake (91.6%). MLRA revealed that having a positive vaccination attitude was 16 times more likely to accept the COVID‐19 vaccination (OR = 16.10; 95% CI 8.97–28.91). Hearing of someone they know who has COVID‐19 serves as a cue to action and significantly influences vaccination (OR = 4.25; 95% CI 1.80–10.03). Participants below 70 years old expressed higher vaccination intention (OR = 2.07; 95% CI 1.19–3.58). Conclusion: The results provide the first evidence for public authorities to target older people vulnerable to compliance with recommended preventive measures against SARS‐CoV‐2 infections.